Penyelesaian Tindak Pidana Melalui Mediasi Penal pada Tingkat Penuntutan berdasarkan Peraturan Kejaksaan Nomor 15 Tahun 2020 Tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif (Studi Pada Kejaksaan Negeri Sijunjung) - Ghifari, Teguh; Zurnetti, Aria; Yasniwati, Yasniwati (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The development of criminal law has encouraged the implementation of penal mediation as an alternative for resolving criminal cases. This study aims to analyze: (1) the resolution of criminal acts through penal mediation based on the Attorney General Regulation Number 15 of 2020 at the prosecution level in Sijunjung District Attorney’s Office; (2) the considerations for appointing a Facilitator Prosecutor within the Restorative Justice framework; and (3) the obstacles in implementing penal mediation. This research employs an empirical legal (sociological) approach with a descriptive method. The findings indicate that the Public Prosecutor acts as a third party facilitating deliberations between the victim and the offender until an agreement is reached; the appointment of a Facilitator Prosecutor considers integrity, competence, communication skills, experience, and caseload; and the main obstacles include negative public perceptions of case termination, limited public understanding of restorative justice, and a short duration for peace-making processes. The study highlights the crucial role of Prosecutors in supporting criminal case resolution through penal mediation.